2004
DOI: 10.5702/massspec.52.1
|View full text |Cite
|
Sign up to set email alerts
|

Water Clusters in Gas Phases Studied by Liquid Ionization Mass Spectrometry

Abstract: Studies of water clusters under atmospheric pressure are very important. In previous methods, however, clusters existing in vacuum at low temperature have been measured. Therefore, the size distributions of observed cluster ions are likely di#erent from those existing at normal conditions. Liquid ionization (LPI) mass spectrometry we have developed provides information about hydrogen-bonded clusters in a gas phase and also at the liquid surface at ambient temperature under atmospheric pressure. Thus, LPI-MS wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…1 may contribute significantly to the observed strong THz emission from water vapour under optical stimulation. Experiment and theory agree that not only can such water clusters be produced but they also occur optimally in certain numbers (so-called magic numbers) and configurations of water molecules [3,[8][9][10]. Prominent among the magic-number water clusters that have been identified are ones having the "buckyball-like" pentagonal dodecahedral structure [9,10] shown in Fig.…”
Section: Introductionmentioning
confidence: 95%
“…1 may contribute significantly to the observed strong THz emission from water vapour under optical stimulation. Experiment and theory agree that not only can such water clusters be produced but they also occur optimally in certain numbers (so-called magic numbers) and configurations of water molecules [3,[8][9][10]. Prominent among the magic-number water clusters that have been identified are ones having the "buckyball-like" pentagonal dodecahedral structure [9,10] shown in Fig.…”
Section: Introductionmentioning
confidence: 95%
“…Measurement of the ion peak intensities allows the determination of quantitative data such as equilibrium constants, heats and enthalpy for individual hydration steps. Mass spectrometric analysis of positive ion water clusters H 3 O + (H 2 O) n has been performed under various experimental conditions such as field emission ionization in water vapor, [6,7] a free jet expansion of water vapor with electron impact, [8,9] liquid ionization, [10] electrospray, [11] discharge ionization, [12] ion bombardment of ice surfaces [13] and near-threshold vacuum-UV photoionization of neutral clusters. [14] The resulting mass spectra consisting of the dominant water cluster ions H 3 O + (H 2 O) n have some common…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a soft ionization method, termed liquid-ionization mass spectrometry for analysing nonvolatile organic compounds, [21][22][23] (referred to as LPI since 1998 22) ), in which a liquid sample is ionized by collision with excited argon atoms (Ar * ) under atmospheric pressure at ambient temperature (23-25°C). The method (LPI-MS) has been also applied to studies of clusters, such as water, 24) carboxylic acid-water mixtures, 25) and reaction products formed in formaline with a small amount of methanol. 26) The distribution of cluster sizes of water in the air has been measured at ambient temperature and found that the size distributions were related to the humidity, 24) suggesting that neutral clusters of water exist in the air.…”
Section: Liquid Ionization (Lpi) Mass Spectrometrymentioning
confidence: 99%
“…The method (LPI-MS) has been also applied to studies of clusters, such as water, 24) carboxylic acid-water mixtures, 25) and reaction products formed in formaline with a small amount of methanol. 26) The distribution of cluster sizes of water in the air has been measured at ambient temperature and found that the size distributions were related to the humidity, 24) suggesting that neutral clusters of water exist in the air. Alcohol aqueous solutions (20%v/v, methanol and ethanol) have been measured by LPI-MS. 27) The molar ratios of alcohol to water calculated from LPI mass spectra have been agreed with the alcohol concentration of the solution, although the flow rate of a sample solution (F s ) and the voltage applied to the needle (V E ) should be controlled.…”
Section: Liquid Ionization (Lpi) Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation